36-72-month-old children mothers’ views about COVID-19 Pandemic - Tunçeli, Hilal İlknur (Southeast Asia Early Childhood Journal, 2022)
This study investigates mothers’ views about the Covid-19 pandemic and how they affect these things and their feelings. The study group includes 58 mothers who have 36-72 months old children. The phenomenological method used in qualitative methods was used in the study, and data were collected by semi-structured interview method. The study data were collected from mothers using the ZOOM online meeting program in the 2020-2021 fall semester. The interview form includes the personal information part and questions to investigate parents' views and feelings about the covid-19 pandemic—the data of the study analyzed by using the MAXQDA software.  According to the findings, mothers' views on the COVID-19 pandemic process focus on order change and anxiety-fear. Many mothers stated that they were negatively affected by the pandemic process due to uncertainty and anxiety about losing their loved ones. It would be useful to consider mothers' thoughts and feelings about the pandemic process from different dimensions, affecting children's perspectives on the process.